2007
DOI: 10.2105/ajph.2006.091892
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Paradox in Biological Risk Profiles

Abstract: Objectives. We examined biological risk profiles by race, ethnicity, and nativity to evaluate evidence for a Hispanic paradox in measured health indicators. Methods. We used data on adults aged 40 years and older (n = 4206) from the National Health and Nutrition Examination Surveys (1999–2002) to compare blood pressure, metabolic, and inflammatory risk profiles for Whites, Blacks, US-born and foreign-born Hispanics, and Hispanics of Mexican origin. We controlled for age, gender, and socioeconomic status. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
218
7
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(253 citation statements)
references
References 51 publications
25
218
7
3
Order By: Relevance
“…Although some previous studies have suggested that foreign-born Mexican American adults may have more favorable risk status compared with those who were US born, 29,30 this finding has not been observed consistently. 31 Kershaw et al reported that foreign-born Mexican Americans adults had almost 3 times higher odds of being LR compared with US-born Mexican American adults.…”
mentioning
confidence: 78%
“…Although some previous studies have suggested that foreign-born Mexican American adults may have more favorable risk status compared with those who were US born, 29,30 this finding has not been observed consistently. 31 Kershaw et al reported that foreign-born Mexican Americans adults had almost 3 times higher odds of being LR compared with US-born Mexican American adults.…”
mentioning
confidence: 78%
“…First, we used a large national sample that included a heterogeneous population of Hispanic subgroups, a major limitation of prior work that has focused largely on Mexicans in 1 geographic region29 and on risk factors rather than mortality 30, 31, 32. US‐born Cubans and Puerto Ricans, in particular, had lower AMRs, suggesting a protective effect of generational status among these subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…For Mexican Americans, unadjusted cardiovascular risk is intermediate between those of whites and blacks but is not significantly different from that of whites after controlling for income, education, and health insurance status. 291 However, the prevalence of risk factors rises with duration of residence in the United States and varies among cultural and ethnic subgroups within the larger group of US Latinos. 270 By income and by educational attainment, 292 disadvantage is associated with higher risk.…”
Section: Socioeconomic Disadvantage and Risk Factors For Cvdmentioning
confidence: 99%